Postpartum major depression at six weeks in primary health care: prevalence and associated factors - Nakku, Juliet EM (Makerere Medical School, 2006)
BACKGROUND: Major depression is a common and disabling complication of the postpartum period in women. It is thought to occur three times more commonly in the developing than in developed countries. OBJECTIVES: The objectives of this study were to determine the prevalence of and factors associated with major depression among women attending a peri-urban primary health care unit in Kampala, Uganda, at six weeks postpartum. METHOD: Five hundred and fourty four women attending a peri-urban health centre were investigated in a cross-sectional study. These women were screened using the twenty five-item Self Reporting Questionnaire (SRQ-25), while major depression was confirmed using the Mini International Neuro-psychiatric Interview (MINI). Associations were sought between major depression and the respondents' demographics and various psychological, social and obstetric factors. RESULTS: The point prevalence of major depression at six weeks postpartum was 6.1%. Psychiatric disorder was significantly associated with young age, being single, negative life events, unplanned pregnancy, unwanted sex of baby and current physical illness in both mother and newborn. CONCLUSION: There is indication for routine screening of at risk women in the peri-natal period to avoid, recognize and manage postpartum psychiatric morbidity and its consequence on mothers and their developing children.